August Schleicher as the First Publisher of Lithuanian Folktales - Šlekonytė, Jūratė (Tautosakos darbai, 2021)
The article focuses on the Lithuanian cultural activities of the famous German linguist August Schleicher (1821–1868). These activities included not only accumulation of linguistic data and writing of a Lithuanian grammar, but also recording and publication of the Lithuanian folklore. Schleicher edited the particularly valuable reader of the Lithuanian language and vocabulary (Handbuch der litauischen Sprache, Bd. 2: Lesebuch und Glossar, 1857), which included the first publication of Lithuanian folktales, among other kinds of folklore. The author of the article aims at elucidating the objectives and circumstances of Schleicher’s recordings of the Lithuanian folktales, establishing of their genres and defining the typical narrative qualities. Besides, the importance of the tales that Schleicher recorded in terms of the Lithuanian folklore research is highlighted. The letters that Schleicher wrote in the course of his research trip to the Eastern Prussia in 1852 reveal the kind of difficulties that he encountered during this journey, his ways of communication and his experiences while collecting the Lithuanian folktales. The folk narratives published in his Lithuanian reader and vocabulary include fifteen tales of magic, seven joke tales, four novella tales, three animal tales, three tales of lying, two tales of the stupid ogre, one religious tale, four folk-belief legends and one local legend. The scholar was the first to record numerous examples of various Lithuanian tale types, which mostly belonged to the popular Lithuanian oral tradition. The linguist himself highly valued his work among the Lithuanian inhabitants of the Lithuania Minor, being well aware that it served to the preservation of the declining culture at least in the scientific purposes. He hoped that folklore recorded and published by himself and his assistants could support the Lithuanians resisting the intense assimilation processes. The results of his research trip in the Lithuania Minor testified to the vitality of the folk narrative tradition among the local Lithuanians in the middle of the 19th century. By researching the Lithuanian language and recording the Lithuanian folklore, Schleicher established the importance of this culture to the Indo-European studies in general and attracted numerous followers that carried on with his scholarly activities. His activities prompted Lithuanians themselves to collect their oral folk heritage as well. Thanks to Schleicher, the first Lithuanian folktales were translated into German, published and attracted notice of the foreign scholars. Their subsequent publications reached even broader social layers. Therefore, Schleicher may be regarded as the promoter of the Lithuanian folktales across other countries. Nowadays the Lithuanian folktales published by Schleicher have been included into various folklore collections as anonymous folklore pieces and have acquired literary interpretations.